Economic Growth and Environment: Tourism as a Trigger for Green Growth. (February 2015) - Marsiglio, Simone
The paper analyses the implications of tourism activities for economic growth and environmental assets, focusing especially on small island countries. The author develops a stylized dynamic economic model in which tourism is the trigger of the incentive mechanism leading to abatement activities and economic growth. The basic idea is that tourists choose the location to visit according to a number of factors (including environmental quality) which are affected by residents' choices. If residents engage in environmental protection activities, it then may be possible for environmentally based tourism economies to reach a smooth development process. The author shows that the (sustainable) balanced growth path is the only viable equilibrium, and along such a path consumption grows while environmental quality rises. Tourists' preferences crucially affect the long-run outcome, since economic and environmental growth rates increase with the green preference and decrease with the grey preference and crowding aversion parameters. Thus, if tourism specialization is to be the pathway to development, green tourism will need to be promoted.